Dual effects of fibroblast growth factor 21 on hepatic energy metabolism - Samms, Ricardo J.; Murphy, Michelle; Fowler, Maxine J.; Cooper, Scott; Emmerson, Paul; Coskun, Tamer; Adams, Andrew C.; Kharitonenkov, Alexei; Ebling, Francis J.P.; Tsintzas, Kostas (BioScientifica, 2015)
The aim of this study was to investigate the mechanisms by which FGF21 affects hepatic integration of carbohydrate and fat metabolism in Siberian hamsters, a natural model of adiposity. Twelve aged matched adult male Siberian hamsters maintained in their long day fat state since birth were randomly assigned to one of two treatment groups and were continuously infused with either vehicle (saline; n=6) or recombinant human FGF21 protein (1 mg/kg/day; n=6) for 14 days. FGF21 administration caused a 40% suppression (P<0.05) of hepatic pyruvate dehydrogenase complex (PDC), the rate-limiting step in glucose oxidation, a 34% decrease (P<0.05) in hepatic acetylcarnitine accumulation, an index of reduced PDC flux, a 35% increase (P<0.05) in long-chain acylcarnitine content (an index of flux through β-oxidation) and a 47% reduction (P<0.05) in hepatic lipid content. These effects were underpinned by increased protein abundance of PD kinase-4 (a negative regulator of PDC), the phosphorylated (inhibited) form of acetyl-CoA carboxylase (ACC, a negative regulator of delivery of fatty acids into the mitochondria), and the transcriptional co-regulators of energy metabolism peroxisome proliferator activated receptor gamma co-activator alpha (PGC1 and sirtuin-1 (SIRT-1). These findings provide novel mechanistic basis to support the notion that FGF21 exerts profound metabolic benefits in the liver by modulating nutrient flux through both carbohydrate (mediated by a PDK4-mediated suppression of PDC activity) and fat (mediated by deactivation of ACC) metabolism, and therefore may be an attractive target for protection from increased hepatic lipid content and insulin resistance that frequently accompany obesity and diabetes.